Performance of the Microalgal Biomass for the microdiesel production from a gap of energy potential - O. Medina-Carpio (2019)
It was identified the energy potential (PE) of biodiesel generated by microproducers in Arequipa is 8042.2495 MJ * Kg-1 obtained from 50 gallons of biodiesel (B100), for this reason the present research work aimed at the implications techniques to reach the main gaps that must be overcome in research and development (R & D) to achieve the desired PE in the microalgal biomass as the main source of transesterified oil, the research showed that it is possible to obtain0.82 g / l Biomass microalgal from Chlorella sp. in a Raceway system managing to extract 614.90 g / kg of oil from dry microalgal biomass at your reach 554.32 g / Kg of transesterified oil (Biodiesel-B100), to carry out an investigation as a model for the ALDECO microenterprise. The results were determined for a microproducer looking for an energy potential (PE) of 8042.2495 MJ Kg-1 with a feasible production potential (PPP) of 50 gal / month implying anarea of 2.35 ha under a yield determined by the available biomass potential (PBD) of 820 g / m3 and of generated fuel (PCG) of 28.55 g / m3 in BBM culture medium.